Fifth Size Strain Conference. Diffraction Analysis of the Microstructure of Materials : Garmisch-Partenkirchen, October 7-9, 2007 (De Gruyter Oldenbourg, 2008)
Zeitschrift für Kristallographie. Supplement Volume 27 presents the complete Proceedings of all contributions to the V Size Strain Conference in Garmisch-Partenkirchen 2007: Lattice Defects Residual Stresses Texture in Thin Films and at Surfaces Line-Broadening Analysis and Line-Profile Fitting Diffraction/Microstructure Modeling Supplement Series of Zeitschrift für Kristallographie publishes Proceedings and Abstracts of international conferences on the interdisciplinary field of crystallography.